Pengaruh Celebrity Endorser, Label Halal, dan E-WoM terhadap Keputusan Pembelian Kosmetik Scarlett Whitening dengan Minat Beli sebagai Variabel Mediasi - Nisa`, Maulida Khoirotun; Guritno, Agung (Studia Economica : Jurnal Ekonomi Islam, 2024)
This research aims to examine the Influence of Celebrity Endorser, Halal Label, and E-WoM on Purchase Decision Mediated by Purchase Interest. This study applies a quantitative method with primary data type and purposive s ampling as the sampling technique. The research was conducted by distributing questionnaires in the form of Google Form through direct links or using QR Codes with a sample size of 210 respondents. Testing was conducted using classic assumption tests, model accuracy tests, and hypothesis tests. The data were analyzed using SPSS version 29. The results of the t-test show that celebrity endorser significantly and positively influences purchase interest, while halal label and E-WoM have a positive but non-significant effect on purchase interest. Additionally, the t-test results indicate that celebrity endorser, halal label, and E-WoM significantly and positively influence purchase decisions. Meanwhile, the Sobel test results show that purchase interest can mediate the influence of celebrity endorser on purchase decisions, but purchase interest cannot mediate the influence of halal label and E-WoM on purchase decisions